Desain Iterasi Dudukan Pelat Pengukur Gaya Pada RIG Alat Uji Jatuh Bebas Menggunakan Optimasi Topology - Maulana, Ilham; A. Sitompul, Sahril; Rabeta, Bismil; Fitriansyah, Rizky; Nurrohmad, Abian (FTK UNSURYA, 2022)
Abstract -. This research was conducted based on data obtained during testing at LAPAN (Lembaga Antariksa dan Penerbangan Nasional), where there was a case that became a concern. The test is about the free fall test, which results in a deflection that is considered too large. From these results it was decided to investigate further. This free fall test uses impact testing where a material is measured for its shock load resistance. Impact testing simulates the operating conditions of a material where the loading that occurs is not only in static conditions but also occurs in dynamic conditions. In the free fall test, a test was carried out to measure and see the resistance of the landing gear and crash box in receiving dynamic loads, when the aircraft landed. The main purpose of simulating this tool is for research and development of the free fall test equipment itself, as well as the design of the landing gear of the LSU (Lapan Survaillance UAV) drone in the future. The impact platform on the free fall test equipment plays an important role in impact testing, where the deformation of the plate holder will be converted by the load cell, into a signal received by the acquisition system. So it is designed to fit the existing needs. In this test equipment, the test object is given a load (50 kg and 200 kg), height (4.72 m and 1,204 m), so that it reaches a velocity (9,623 m/s and 4,861 m/s) with impactor crash box geometry and main landing gear as well as plate holder design based tools in the field. Based from testing, impact, and analysis using the finite element method in this study, it was found that the deflection value was 1.771 mm which reduced 94.61% for the crash box case and the deflection value was 2.696 mm with a reduction value of 87.85 % for the main landing gear case from the existing initial design. Keywords: Free fall test equipment, impact platform, landing gear, plate mount, main landing gear, crash box, finite element method, LSU.